Tecnologias emergentes no setor portuário: um estudo no setor portuário brasileiro - RESENDE, Renilson José Silva (2023)
In recent years, the port industry has faced escalating challenges regarding its sustainability, as the demand for maritime transportation in the global economy has continued to grow. To address these challenges, ports have been adopting emerging technologies to enhance their efficiency, safety, and sustainability. The results of the bibliometric review revealed that the Internet of Things (IoT) has been one of the most addressed technologies. IoT serves as the foundation for other technologies, such as artificial intelligence and autonomous systems, being applied in ports to automate processes and improve decision-making. Countries with established traditions in maritime transportation, such as Germany, China, Spain, the United States, Greece, and the Netherlands, have led research and development in this field. Artificial intelligence and autonomous systems have the potential to reduce pollutant emissions and optimize the use of energy resources, contributing to sustainability. Additionally, real-time monitoring technologies assist in identifying and mitigating environmental risks, promoting safer and more sustainable port operations. In the Brazilian context, the increasing demand for maritime transportation has encouraged the adoption of emerging technologies in major ports. Technologies like radar, data lakes, telemetry, and augmented reality are being applied to enhance the efficiency, quality, and sustainability of port operations. Leading companies such as Vale, Transpetro, Amaggi, and Mineração Rio do Norte are at the forefront of adopting emerging technologies due to their commitment to innovation and socio-environmental responsibility. Overall, emerging technologies are driving substantial improvements in port operations, reflecting a commitment to innovation and sustainability while paving the way for the adoption of even more advanced technologies. As a limitation in the study, it was identified that the reports do not distinguish technologies exclusively applied in port logistics. The following future research opportunities were identified: evaluating the real impact of emerging technologies on the efficiency, safety, and sustainability of Brazilian port operations; investigating how mentioned technologies are being adopted by smaller ports in Brazil; understanding how various mentioned technologies are being integrated and coordinated in Brazilian ports; exploring the long-term sustainability effects of these technologies on Brazilian ports; conducting a comparison between technology adoption in ports and other transportation sectors in Brazil; analyzing how public policies encourage or hinder technology adoption in Brazilian ports; exploring how technological innovations in ports are affecting local communities in terms of employment, environment, and quality of life; investigating cybersecurity in Brazilian ports; analyzing how port workers are being trained and empowered to effectively use these technologies, and conducting a comparison between technological innovations in Brazilian ports and ports in other countries. This work presents the author's firsthand experience with the studied technologies in the professional context at Vale, providing a real-world perspective on this sustainability- related theme.